Podcasting as a Tool for Developing Oral Proficiency and Self-regulated Learning Strategies: Insights from Turkish EFL Learners - Akyıldız, Seçil Tümen (My University, 2024)
This study examines the impact of podcasts on high school students' English language learning, focusing on speaking performance and self-regulated learning strategies. The widespread adoption of digital communication technologies has transformed education, necessitating the integration of technology to enhance learning outcomes. Using a qualitative approach, the study investigates the general English learning habits of students, their perceptions of using podcasts to improve speaking skills, and how podcasts influence their ability to self-regulate learning. Findings reveal that students actively engage with English-language media, benefiting from enhanced listening comprehension, vocabulary acquisition, and pronunciation. Recording podcasts fosters confidence and fluency in speaking, while also promoting goal setting, planning, and reflective practices. The study highlights the importance of integrating podcasts into EFL instruction to create a dynamic learning environment that supports students' language proficiency goals. The results contribute to the literature on educational technology and underscore the potential of podcasts to improve language learning experiences.
Keywords: EFL; podcast; self-regulation; speaking skills